Perilaku Pedagang Pasar Pabean Surabaya Dalam Perspektif Prinsip Dasar Pasar Islami - Harmain, Rizky Imani; Fikriyah, Khusnul (Universitas Negeri Surabaya, 2023)
In buying and selling activities, it is only natural for traders to seek profit, but because of the high competition between traders, traders justify any means to pursue profits and even traders ignore ethics in doing business. This is inversely proportional to what the Prophet did, the Prophet Muhammad SAW was a professional trader in buying and selling his wares, he was known as an honest person in doing business and this became the basis for many people to believe in him. This study aims to determine the behavior of Surabaya Customs market traders in the perspective of the basic principles of Islamic markets. This type of research uses descriptive qualitative research. data collection techniques using observation, interviews and documentation. The results showed that the behavior of traders in the Customs market was quite good, but the behaviorof traders needed to be improved in terms of the accuarcy of measuring the scales. In fact, they did not find fraud in terms of scales, but the scales had not been re-calibrated by the relevant officers for the last 5 years. And traders in the Customs market have implemented the basic principles of the Islamic market even though the Customs market is an ordinary traditional market or a conventional market and not a sharia market that applies sharia principles in it. The basic principles of the Islamic market include the principles of Ar-Rida, the principles of fair competition, the principles of honesty, the principles of openness and the principles of fairness.